2016
DOI: 10.1134/s1607672916020101
|View full text |Cite
|
Sign up to set email alerts
|

EPR spectroscopy solutions for assessment of decellularization of intrathoracic organs and tissues

Abstract: Using EPR spectroscopy it was established that the determination of the concentration of paramagnetic centers in lyophilized tissues allows indirect evaluation of the quality of decellularization of intrathoracic organs (diaphragm, heart, and lungs), since the content of paramagnetic particles in them can serve as a criterion of cell viability and points to the necessity to repeat decellularization. Experiments in rats showed that the EPR spectra of the native thoracic organs contained paramagnetic centers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…This protocol allowed viable and functional scaffolds to be obtained, with high biocompatibility, pro-angiogenic, and pro-regenerative potential, which demonstrated to be re-innervated after implantation into a GFP+ Schwann cell mouse model [27][28][29][30]. The same detergentenzymatic treatment proved to be effective on producing acellular rat diaphragm [31], which was also efficiently decellularized by muscle perfusion via vena cava [32,37,38], or immersion [33,36] in solutions of SDS, DNase-I, and ethylenediaminetetraacetic acid (EDTA). Another documented protocol for rat diaphragm decellularization was based on the use of SDS and PBS washes [34], while Sesli and collaborators [35] demonstrated that the use of SDS+Triton X-100 produced cytocompatible acellular scaffolds in comparison with freezing/thawing method plus immersion in sodium chloride (NaCl), which caused severe tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This protocol allowed viable and functional scaffolds to be obtained, with high biocompatibility, pro-angiogenic, and pro-regenerative potential, which demonstrated to be re-innervated after implantation into a GFP+ Schwann cell mouse model [27][28][29][30]. The same detergentenzymatic treatment proved to be effective on producing acellular rat diaphragm [31], which was also efficiently decellularized by muscle perfusion via vena cava [32,37,38], or immersion [33,36] in solutions of SDS, DNase-I, and ethylenediaminetetraacetic acid (EDTA). Another documented protocol for rat diaphragm decellularization was based on the use of SDS and PBS washes [34], while Sesli and collaborators [35] demonstrated that the use of SDS+Triton X-100 produced cytocompatible acellular scaffolds in comparison with freezing/thawing method plus immersion in sodium chloride (NaCl), which caused severe tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, human diaphragm harvested from cadavers was considered as an ideal, but still little investigated, source for the development of decellularized biological scaffolds for VML treatment. To the best of our knowledge, only 13 works in the literature have reported the decellularization of the diaphragmatic muscle [27][28][29][30][31][32]34,[39][40][41][42][43][44], plus 5 research articles that considered the diaphragm together with other tissues for methodological studies about decellularization procedures or analysis techniques validating acellular ECM quality [33,[35][36][37][38] (Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Krasnodar group has recently examined both quantitative and qualitative non-invasive evaluation tools for verification of decellularization efficiency. [11,35,44,45] Accordingly: 1) quantitative determination of cell viability through electron paramagnetic resonance spectroscopy; and 2) monitoring free radical generation through chemiluminescence may serve as objectifiable decellularization quantification tools. Ultrasound imaging as a clinically proven safe examination method can likewise be employed for decellularized, as well as recellularized tissues through high-frequency acoustic microscopy prior to implanta-www.advancedsciencenews.com www.advtherap.com tion.…”
Section: Pre-implantation Evaluation Tools For Decellularization-base...mentioning
confidence: 99%
“…1) и подтверждало присутствие клеток, в отличие от децеллюляризированных тканей, в которых отсутствовал ЭПР-сигнал с g-фактором в диапазоне от 2.005 до 2.012. Полученные результаты указывают на целесообразность использования ЭПР-спектроскопии для оценки жизнеспособности клеточных структур в нативных тканях, в которых функционирование системы переносчиков электронов, прежде всего в митохондриях, является причиной образования свободных радикалов, участвующих также в обеспечении жизнедеятельности клеточных структур [4,15].…”
unclassified